2020
DOI: 10.1101/2020.09.10.292326
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modular barcode beads for microfluidic single cell genomics

Abstract: Barcode beads allow efficient nucleic acid tagging in single cell genomics. Current barcode designs, however, are difficult to extend to novel targets, or alter to add additional targets as information is obtained. Here, we describe a modular framework that simplifies generation of multifunctional beads and allows their easy extension to new targets.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…We here instead immobilized high copy numbers of DNA templates on streptavidin-coated beads. Such beads are used for single-cell sequencing protocols and therefore widely available [42,43]. We showed that in-droplet protein expression from a single DNA-loaded bead is similar to cell-free expression from DNA in solution.…”
Section: Discussionmentioning
confidence: 99%
“…We here instead immobilized high copy numbers of DNA templates on streptavidin-coated beads. Such beads are used for single-cell sequencing protocols and therefore widely available [42,43]. We showed that in-droplet protein expression from a single DNA-loaded bead is similar to cell-free expression from DNA in solution.…”
Section: Discussionmentioning
confidence: 99%
“…To generate beads with barcoded primers, acrylamide precursors are combined microfluidically and polymerized in water-in-oil droplets with an acrydited primer. Polyacrylamide beads containing the bound primer are removed from oil using 1H,1H,2H,2H-Perfluoro-1-octanol (Sigma-Aldrich), and barcodes are added using a split-pool ligation-based approach …”
Section: Methodsmentioning
confidence: 99%
“…Cascade Blue is included as a drop dye to enable the merging of all drops as an experimental control. Custom barcode beads are generated as recently described, 25 targeting 16 amplicons of the Mission Bio Acute Myeloid Leukemia panel (Table S1). These amplicons are chosen because K562 and CEM have different single-nucleotide polymorphisms (SNPs) in those genomic locations that allow for their subsequent identification.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the preparation of nuclei for scRNA-seq, we used a modified protocol from the recently published single nuclei preparation toolbox 37 to extract nuclei from snap-frozen mouse cortex samples. Briefly, a ~1 cm 3 frozen piece of mouse cortex tissue was transferred to 0.5 mL of icecold homogenisation buffer (Salt-tris solution -146 mM NaCl, 10 mM Tris 7.5, 1 mM CaCl2, 21 mM MgCl2, 250 mM Sucrose, 0.03% Tween-20, 0.01% BSA, 25 mM KCl, 1 mM 2-Mercaptoethanol, 1X cOmplete protease inhibitor, 0.5U/ul of RNAse In Plus (Promega)) in a Dounce homogenizer mortar and thawed for 2 minutes.…”
Section: Snap-frozen Mouse Cortex Nuclei Extractionmentioning
confidence: 99%